ISLAM, CADAR, JILBAB DAN BURQA DALAM AL-QUR’AN - Mumun Munawarotul Hasanah; Pirda Raudatul Jannah; Rabbani Pasha Ababyl; Rafi Daffa Musyaffa (Nusantara Hasana Journal, 2023)
The Qur'an has properly regulated the way women dress to cover their nakedness. In fact, the directives are specifically so that women are able to maintain their honor. Whether we realize it or not, as time goes by, covering the genitals becomes more varied and diverse. This causes the awareness of Muslim women to wear the hijab properly decreases. One example is by wearing the hijab to follow the trend to make it look contemporary. The purpose of this research is to provide Muslim women with an understanding of how to properly cover their genitals based on the Qur'an and its interpretations. This type of research is qualitative with data collection through library research. Then it is developed with descriptive analysis to further explain a meaning. The results of this study are that there are 3 verses of the Qur'an which explain the covering of the genitals, including lafadz khimar (QS. An-Nur verse 31), hijab (QS. Al-Ahzab verse 53) and lafadz jilbab (QS. Al-Ahzab -Ahzab verse 59). Khimar, as an order, guards his eyes and private parts, nor does he reveal his jewelery (beauty of the body). Lafadz Hijab is intended to cover the entire body so that it is not visible from the body except for the eyes. While lafadz hijab is that it must cover the entire body, including the face, palms, voice and body shape should not be seen.